Total ozone decrease in the Arctic after REP events - Roldugin, V. C.; Beloglazov, M. I.; Remenets, G. F. (HAL CCSD, 2000)
International audience Eight periods of relativistic electron precipitation (REP) with electron energies of more than 300 keV are identified from VLF data (10-14 kHz) monitored along the Aldra (Norway) - Apatity (Kola peninsula) radio trace. In these cases, anomalous ionization below 55-50 km occurred without disturbing the higher layers of the ionosphere. The daily total ozone values in Murmansk for six days before and six days after the REP events are compared. In seven of eight events a decrease in the total ozone of about 20 DU is observed. In one event of 25 March, 1986, the mean total ozone value for six days before the REP is bigger than that for six days after, but this a case of an extremely high ozone increase (144 DU during the six days). However, on days 3 and 4 there was a minimum of about 47 DU with regard to REP days, so this case also confirms the concept of the ozone decrease after REP. The difference between mean ozone values for periods six days before and six days after the REPs was found also for 23 points in Arctic on TOMS data. The difference was negative only in Murmansk longitudinal sector. Along the meridian of the trace it was negative at high latitudes in both hemispheres and was near zero at low latitudes.